Unveiling common responses of Medicago truncatula to appropriate and inappropriate rust species - Vaz Patto, Maria Carlota; Rubiales, Diego (Frontiers in Plant Science, 2014)
Little is known about the nature of effective defense mechanisms in legumes to pathogens of remotely related plant species. Some rust species are among pathogens with broad host range causing dramatic losses in various crop plants. To understand and compare the different host and nonhost resistance responses of legume species against rusts, we characterized the reaction of the model legume Medicago truncatula to one appropriate (Uromyces striatus) and two inappropriate (U. viciae-fabae and U. lupinicolus) rusts. We found that similar pre and post-haustorial mechanisms of resistance appear to be operative in M. truncatula against appropriate and inappropriate rust fungus. The appropriate U. striatus germinated better on M. truncatula accessions then the inappropriate U. viciae-fabae and U. lupinicolus, but once germinated, germ tubes of the three rusts had a similar level of success in finding stomata and forming an appressoria over a stoma. However responses to different inappropriate rust species also showed some specificity, suggesting a combination of non specific and specific responses underlying this legume nonhost resistance to rust fungi. Further genetic and expression analysis studies will contribute to the development of the necessary molecular tools to use the present information on host and nonhost resistance mechanisms to breed for broad-spectrum resistance to rust in legume species.